Unleashing the transformative potential of transitions: context, complementarities and competition - Bento, N.; Fontes, M.; Andersen, A.D. (10th International Sustainability Transitions Conference, 2019)
Several low-carbon innovations promise to accelerate the energy transition but only a few engender transformative socio-economic effects. This paper asks under which conditions the development of new technological systems induce changes in other sectors. The literature review reveals three factors that influence the transformative potential of innovations: context; complementarities; and competition. We use a new approach to track the dynamics of these factors by focusing on the extent and the nature of induced activities in adjacent sectors. We apply this framework to study the development of marine renewable energies technologies (MRET) in Portugal, and compare it with Norway. We perform a sectoral mapping and a survey of firms in Portugal. Adjacent sector firms active in several MRET exhibited a higher diversified activity, innovation and organizational change. Comparing with Norway, where the presence of an offshore industry (oil & gas) accelerates the emergence of offshore wind, its absence in Portugal raises challenges but also creates opportunities for the transformation of several sectors. We develop a new indicator to identify and compare the transformative potential of innovations. The results reveal potential for MRET in Portugal and trade-offs between technology readiness and transformativeness.